2018
DOI: 10.1152/ajplung.00289.2018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human PDGFR-β-positive pericytes from IPF and non-IPF lungs

Abstract: Pericytes are key regulators of the microvasculature through their close interactions with the endothelium. However, pericytes play additional roles in tissue homeostasis and repair, in part by transitioning into myofibroblasts. Accumulation of myofibroblasts is a hallmark of fibrotic diseases such as idiopathic pulmonary fibrosis (IPF). To understand the contribution and role of pericytes in human lung fibrosis, we isolated these cells from non-IPF control and IPF lung tissues based on expression of platelet-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 46 publications
(73 reference statements)
2
45
0
Order By: Relevance
“…In addition, pericytes were tagged by PDGFR‐β antibody and it was found that on average 88% of the NG2‐positive cells were also positive for PDGFR‐β. Previous studies have shown that PDGFR‐β is a valid marker of pericytes, for example, 40 and although a large fraction of the pericytes was indeed positive, a smaller fraction of the Ulex1 positive cells were also positive to this marker. Western blot of endothelial cells revealed presence of PECAM‐1 (CD31) and VE‐cadherin which were absent in the pericyte populations.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, pericytes were tagged by PDGFR‐β antibody and it was found that on average 88% of the NG2‐positive cells were also positive for PDGFR‐β. Previous studies have shown that PDGFR‐β is a valid marker of pericytes, for example, 40 and although a large fraction of the pericytes was indeed positive, a smaller fraction of the Ulex1 positive cells were also positive to this marker. Western blot of endothelial cells revealed presence of PECAM‐1 (CD31) and VE‐cadherin which were absent in the pericyte populations.…”
Section: Discussionmentioning
confidence: 92%
“…Increased production of proinflammatory molecules by pericytes in the lungs of mice can be detected as early as six hours after the experimental administration of LPS [67]. Another reported characteristic of pericytes in other tissues is the ability to respond not only to PAMPs but also to DAMPs by secreting proinflammatory cytokines, as demonstrated in pericytes from the lungs of mice [67] and humans [68], and in human placental pericytes [69]. Secretion of inflammatory cytokines by HSCs after stimulation with DAMPs has not been demonstrated in vivo yet, even though an HSC cell line has been shown to exhibit greater expression of activation markers after stimulation with the DAMP high-mobility group box 1 (HMGB1) [70].…”
Section: Pericytes Favor Inflammation At the Early Moments After Injurymentioning
confidence: 96%
“…Isolation and culture of PDGFRb + lung pericytes. Pericytes were isolated from macaque lungs, as previously described (36). Briefly, single-cell lung digests were plated and expanded in Pericyte Medium (ScienCell) to enrich for pericytes (2) and then underwent negative selection for endothelial, epithelial, and leukocyte markers, followed by positive selection for PDGFRb.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, single-cell lung digests were plated and expanded in Pericyte Medium (ScienCell) to enrich for pericytes (2) and then underwent negative selection for endothelial, epithelial, and leukocyte markers, followed by positive selection for PDGFRb. Previously isolated pericytes from HIVÀ human lungs (36) were cultured from frozen stocks. We confirmed absence of a-smooth muscle actin expression by RT-PCR and immunofluorescence.…”
Section: Methodsmentioning
confidence: 99%